1996
DOI: 10.1073/pnas.93.24.13677
|View full text |Cite
|
Sign up to set email alerts
|

Fidelity of RNA polymerase II transcription controlled by elongation factor TFIIS

Abstract: Fidelity of DNA and protein synthesis is regulated by a proofreading mechanism but function of a similar mechanism during RNA synthesis has not been demonstrated. Analysis of transcriptional fidelity and its control has been hampered by the necessity to employ complex DNA templates requiring either a promoter and initiation factors or 3-extended templates. To circumvent this difficulty, we have created an RNA-DNA dumbbell template that can be recognized as a template-primer and extended by RNA polymerase II. B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
120
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(129 citation statements)
references
References 26 publications
9
120
0
Order By: Relevance
“…This may be the extreme case of the preference to cut the nascent RNA just 5Ј of an unstable RNA-DNA base pair, demonstrated for Pol III (30). This extends observations made on RNA-DNA ''dumbbell'' templates, using Pol IIϩTFIIS (22). Importantly, in our study, the rates of both cleavage and extension are measured under physiologically more relevant conditions, within authentic ternary complexes halted on a class III gene.…”
Section: Mechanics Of Error Avoidance and Error Correction By Pol IIIsupporting
confidence: 59%
See 1 more Smart Citation
“…This may be the extreme case of the preference to cut the nascent RNA just 5Ј of an unstable RNA-DNA base pair, demonstrated for Pol III (30). This extends observations made on RNA-DNA ''dumbbell'' templates, using Pol IIϩTFIIS (22). Importantly, in our study, the rates of both cleavage and extension are measured under physiologically more relevant conditions, within authentic ternary complexes halted on a class III gene.…”
Section: Mechanics Of Error Avoidance and Error Correction By Pol IIIsupporting
confidence: 59%
“…Only the fidelity of the mRNA-synthesizing Pol II has been investigated to date. The selectivity of Pol II for the correct NTP was measured in vitro (21), and, paralleling the situation in E. coli, the role of TFIIS, the Pol II cleavage-stimulatory factor, in permitting efficient proofreading was determined (21,22). Interestingly, at least in the yeast Saccharomyces cerevisiae, the errors committed by Pol II during the synthesis of mRNAs may be masked by the higher error-rate of mRNA translation (23).…”
mentioning
confidence: 99%
“…This backtracking is followed by endonucleolytic cleavage of the 3′ RNA fragment carrying the error, which can be promoted by transcription factors GreA and GreB in prokaryotes, or by TFIIS in eukaryotes (96,125,126). Single-molecule experiments provide compelling support for this model, showing that the frequency of long pauses increases in the presence of the nucleotide analog ITP, which mimics misincorporation, and that long pauses lead to enzyme backtracking by an average of ~5 bp.…”
Section: Off-pathway Eventsmentioning
confidence: 66%
“…It has been demonstrated that RNA transcription and translation work with a high degree of fidelity (17)(18)(19). Defining errors during the process of RNA transcription is conceptually straightforward because the incorporation of new nucleotides is template-directed.…”
Section: Resultsmentioning
confidence: 99%